A Review of Factors Affecting Consumer Behavior towards Online Shopping - Harmanjot Kaur; Roopjot Kochar (International Journal of Engineering and Management Research, 2018)
Online shopping is a form of electronic commerce which allows consumers to directly buy goods or services from a seller over the Internet using a web browser. Online shopping provides a good example of business revolution. E-commerce has made life Simple and innovative of individual and groups. Consumer behavior on online shopping is different from physical market where he/she has access to see the products online shopping sites are fast replacing traditional or physical shops. Over, the years the trust of the customers for online shopping sites has increased considerably. The increase in the number of these sites on one hand has led to a fierce competition which means better and cheaper products for customers. However, at the same time customers have their privacy concerns when it comes to shopping online. Internet is changing the way consumers shop and buy goods and services and has rapidly evolved into a global phenomenon. The technology oriented factors like guaranteed quality, cash on delivery discounts and promotions are the major specific factors influencing customer’s attitudes toward online shopping. This research paper attempts to analyze the consumer behavior towards online shopping and the various factors influencing trend of online shopping.